2016
DOI: 10.1097/qai.0000000000001150
|View full text |Cite
|
Sign up to set email alerts
|

Precursor Forms of Vitamin D Reduce HIV-1 Infection In Vitro

Abstract: VitD reduces HIV-1 infection in T cells possibly by inducing antiviral gene expression, reducing the viral co-receptor CCR5 and, at least at the highest cholecalciferol concentration, by promoting an HIV-1-restrictive CD38HLA-DR immunophenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 57 publications
6
28
2
Order By: Relevance
“…[204][205][206][207] This effect may be partially explained by the fact that sufficient VitD levels can reduce inflammation and T cell activation, restrain HIV-1 infection in T cells, and promote the proliferation of CD4 + T cells induced by APCs. 207,208 These observations suggest that the baseline metabolic characteristics may be associated with impaired immune reconstitution in HIV-1-infected individuals during ART.…”
Section: Host Metabolic Factorsmentioning
confidence: 91%
See 1 more Smart Citation
“…[204][205][206][207] This effect may be partially explained by the fact that sufficient VitD levels can reduce inflammation and T cell activation, restrain HIV-1 infection in T cells, and promote the proliferation of CD4 + T cells induced by APCs. 207,208 These observations suggest that the baseline metabolic characteristics may be associated with impaired immune reconstitution in HIV-1-infected individuals during ART.…”
Section: Host Metabolic Factorsmentioning
confidence: 91%
“…Several studies have demonstrated that baseline VitD deficiency in HIV‐1‐infected individuals was associated with diminished CD4 + T‐cell recovery after ART initiation . This effect may be partially explained by the fact that sufficient VitD levels can reduce inflammation and T cell activation, restrain HIV‐1 infection in T cells, and promote the proliferation of CD4 + T cells induced by APCs . These observations suggest that the baseline metabolic characteristics may be associated with impaired immune reconstitution in HIV‐1‐infected individuals during ART.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…Vitamin D induces antiviral gene expression, reduces the viral co-receptor CCR5 on CD4+ T-cells, and promotes an HIV-1-restrictive CD38+HLA-DR+ immunophenotype in in vitro assays, leading to HIV-1 infection inhibition in T cells ( 109 ). Likewise, VitD reduces the ability of TNFα to upregulate the transcription of HIV RNA from latently infected CD4+ cells ( 110 ).…”
Section: Vitd and The Immune Systemmentioning
confidence: 99%
“…In support of this, VD supplementation attenuated HIV-1 replication and increased the number of circulating leukocytes from 100 VD 3 -fed healthy adults [142]. In in vitro experiments using PBMC infected with HIVBa-L, VD treatment reduced HIV-1 infection in T cells by inducing antiviral gene expression and reducing the levels of viral co-receptor CCR5 [143]. In ex vivo experiments using PBMC from seronegative individuals infected with HIV-1, VD treatment was able to reduce HIV-1 transmission by specifically modulating the activation of T cells and the production of antiviral factors [144].…”
Section: Effect Of Vd On Hi Infection Immune Response Pathogenesismentioning
confidence: 74%